PENGARUH PENERAPAN CORPORATE GOVERNANCE, KEBERADAAN DEWAN DIREKSI PEREMPUAN DAN STRUKTUR KEPEMILIKAN TERHADAP NILAI PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Meiana Maulida Hikmawati (EKOBIS, 2022)
Corporate governance has important role to drive firm values creation. The aim of this study is to analyze the influence of corporate governance consisting of independent commissioner, women on board, audit committe, managerial ownership and institutional ownership on value of the firms listed in BEI in 2016-2020 with the adding of control variables. This study will provide an illustration on how corporate governance practices become a value creation source for the firms. There are a total of 510 companies listed in BEI. Using a purposive sampling method, 128 companies were selected as samples. The 2016-2020 annual reports of the companies are used as secondary data source of this research. This study using multiple linear regresision analysis. The results indicate that only independent commissioner, women on board and institutional ownership had positive and significant affects firm’s value.